“TOLAK BALA”: REPRESENTASI BEROKAN SEBAGAI GAGASAN KARYA SENI GAMBAR - Hartono Hartono; Supriatna Supriatna; Nandang Gumelar (ATRAT: Jurnal Seni Rupa, 2020)
In this final assignment, the writer brings up the art in the Indramayu region since the myths and values contained in the art aroused the writer’s interest to present the Berokan art in a drawing. From the studies, the writer has learned that Berokan is considered a medium to ward off misfortune. Strong beliefs held by Indramayu community in the power governing the world have encouraged them to create a kind of art that is not only entertaining, but also spiritual which functions as an intermediary between men and God to convey men’s prayer for protection from calamities, illnes, and disasters. Therefore, in this work which departed from the meaning of “ward off misfortunes”, the writer aims to include and communicate that meaning through the drawing by elaborating symbols, colors, contrasts between light and dark, and composition.Keywords: Berokan, Warding off misfortune, Drawing, Symbols________________________________________________________________ Pada pengkaryaan tugas akhir kali ini penulis mengangkat tentang kesenian yang ada di daerah Indramayu, mitos dan juga nila-nilai yang terkandung dalam kesenian ini menggugah minat penulis untuk mengangkat kesenian Berokan kedalam karya drawing. Dari apa yang sudah penulis dapat tentang Berokan, yang mana Berokan dianggap sebagai media penolak bala. Keyakinan masyarakat di Indramayu yang kuat terhadap kekuatan yang mengatur dunia membuat mereka menciptakan suatu kesenian yang tak hanya sebagai kesenian hiburan semata, kesenian sebagai perantara doa kepada yang Maha Kuasa agar dihindarkan dari segala macam musibah, penyakit, bencana. Oleh karena itu pada pengkaryaan ini berangkat dari makna “tolak bala” tersebut penulis mencoba memasukan dan mengkomunikasikan makna itu melalui media karya drawing dengan simbol-simbol, warna, gelap terang, komposisi.Kata Kunci: Berokan, Tolak Bala, Drawing, Simbol